Nazwy osobowe w opowiadaniach Agnieszki Zimnowodzkiej jako tekstowy komponent dziecięcej konceptualizacji świata - Łuc, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The subject of the article is a selection of personal names excerpted from „Humorki” ( Little Humours ) – a cycle of short stories by Agnieszka Zimnowodzka, which constitute, in the author’s opinion, an important component of a literary communication that reproduces children’s conceptualization of the world. Their specificity, mechanisms of creation and motives for selection were determined by: the addressee’s age, the author’s creative intention, the applied genre and stylistic convention, the functions attributed to namesand subordinated to text pragmatics. The collected set of names was interpreted in the motivational-communicative platform as text and as semiotic and semantic structures. An analysis of the collected anthroponyms revealed a few creative tendencies typical of the writer’s creative workshop. By creating proper names with appellative bases pointing to the characters’ qualities, she follows children’s conceptualization of the world based on trying to experiment with the language. Therefore, the names have a form of naming neologisms derived by means of word building. In the acts of creating proper names, the author applies some particular naming models, within which the names created in series can be indicated. The writer brings together personal names and other onymic categories which complete their meanings and maximise the power of the message, making use of both verbal and situational humour.